Pendidikan Anti Korupsi terhadap Siswa dan Siswi Sekolah Menengah Kejuruan di Salatiga - Marihot Janpieter Hutajulu; Sri Harini Dwiyatmi; Christina Maya Indah S.; Belby Sahyang Binela; Rachel Angeline Saragih (Jurnal Hukum Lex Generalis, 2024)
The title of this article is “Anti-corruption Education for Students and Vocational High School Students in Salatiga”. The purpose of the implementation of this activity is to disseminate anti-corruption education to the community, in this case for the younger generation. The method of implementation is by conducting socialization and training by using game tools to the participants. The results of this anti-corruption education provide more understanding to the participants about the basic concepts of corruption, corruption crimes, corruption behaviors, and how to prevent corruption with anti-corruption education. In this case, students are expected to become agents of change and the agents help to socialize anti-corruption education to other students, friends and the wider community. Corruption is a crime that destroys the joints of the state, so the government and the people of Indonesia society should have a zero tolerance towards corruption, namely advancing anti-corruption education from an early age and making it a subject in schools.